Development of a pneumatic soft actuator with pleated inflatable structures. (18th July 2017) - Nishioka, Yasutaka; Uesu, Megumi; Tsuboi, Hisae; Kawamura, Sadao; Masuda, Wataru; Yasuda, Toshihiko; Yamano, Mitsuhiro
Abstract: Many soft actuators have been studied for use in robots that come into contact with humans, including communication, entertainment, and medical/health care robots. One reason for this is that soft robots are expected to exhibit intrinsic safety in case an accident occurs. This paper proposes a plastic-film pneumatic actuator with a pleated structure that do not undergo the elastic deformation typical of rubber materials. By utilizing thin plastic films, the mass of an actuator can be significantly reduced, even if the actuators are the same size as a human arm. If the mass of the actuator is reduced, the kinetic energy when contacts with humans mechanically can be reduced considerably without reducing the working speed. More specifically, we propose a pleated structure made of plastic to achieve structural deformation generated from a two-dimensional pleated film. The pleated structure easily generates various bending motions. In this paper, a design method for determining the shape parameters of the pleated actuator structure using approximate models with considering measurement results of generating force is presented. We evaluated the adequacy of our approach in experiments using sample actuators. Furthermore, we show the constraints required to determine the necessary parameters. Thus, this paper provides an easy method for designing a lightweight and flexible plastic-film actuator. Abstract :